Transaksi Non Tunai sebagai Determinan Efisiensi Belanja Pemerintah Daerah Provinsi Riau - Tia Weldison; Dahlan Tampubolon; Ritayani Iyan (Universitas Bengkulu, 2021)
This study analyzes the influence of non-cash transactions, regional own revenue, and the ratio of fiscal decentralization on the efficiency of regional expenditure. The research was conducted in Riau Province using secondary data such as regional expenditure, non-cash transactions, and regional own revenues of Riau Province in 2010-2019. Multiple regression analysis is used to examine the influence of non-cash transactions, fiscal decentralization ratios, and local revenue on the efficiency of regional spending. The study results show that non-cash transactions and regional own revenue have a significant and negative effect on the efficiency of regional expenditure in Riau Province. Fiscal decentralization has had a significant and positive influence on the efficiency of regional expenditure in Riau Province in 2010-2019. The non-cash transaction variable is the variable that most influences the efficiency of regional expenditure.